Avaliação da toxicidade e atividade antiartrítica do óleo essencial de folhas de Baccharis dracunculifolia DC (asteraceae) em camundongos - Lima, Joyce Almeida (2024)
Baccharis dracunculifolia is a plant widely used in Brazilian traditional medicine due to its attributed medicinal properties, including anti-inflammatory and antioxidant activities. Given the impact of these significant diseases on quality of life and the challenges associated with conventional treatments, it is relevant to investigate therapeutic alternatives based on natural products, evaluating both their efficacy and safety. The main objective was to investigate the toxicity and antiarthritic effect of the essential oil extracted from the leaves of Baccharis dracunculifolia in mice. Specifically, the objectives include the protection and characterization of the essential oil, the evaluation of its toxicity, and the analysis of its anti-arthritic effect in mice. The study methodology involves the treatment of antiarthritic activity in female Swiss mice for 14 days with different doses of Baccharis dracunculifolia essential oil (BcEO), at dosages of 25, 50 and 100 mg/kg. The experimental model used was Freund's complete adjuvant-induced arthritis (CFA). The results showed a significant reduction in paw edema and plasma concentrations of TNF-alpha and IL-1beta in the BcEO-treated groups. In addition, there was a significant increase in the levels of superoxide dismutase and catalase, and a decrease in the levels of malondialdehyde, decreasing a positive modulation of oxidative stress. Macroscopic imaging revealed a specific increase in soft tissue inflammation and bone deformities in the control group, while mice treated with BcEO showed minor pathological changes, similar to those seen in the group treated with indomethacin, a conventional anti-inflammatory. In conclusion, the essential oil of Baccharis dracunculifolia leaves showed significant antiarthritic effect, reducing edema, proinflammatory cytokines, and oxidative stress in the model of CFA-induced arthritis in mice. In addition, it showed a promising safety profile, with no signs of toxicity or impact on animal homeostasis after acute or repeated dosing. These results highlight the essential oil's potential as a candidate for natural anti inflammatory therapies.